In a few hands : monopoly power in America - Kefauver, Estes; Till, Irene; Block, Herbert (New York, Pantheon Books, 1965)
The late Senator Kefauver (1903-63) repeatedly went searching for organized crime with a television camera. The wisdom he learned from his first large experience of this search (1950-51) was then expressed in his dedication of a book* (3z$1! =(Bto the people of America, who, I hope, will be sufficiently aroused to help us, through public opinion and legislative action, to strangle crime in America$1! =(3y (BHe seems never to have entirely outgrown the faith of those who go out righteously to strangle what is criminal, and will be done with the task before the setting of the sun.s
Includes bibliographical footnotes.
lje 13/06/17
Loans
Keywords: Monopolies; Trusts, Industrial; Competition